Estimative analysis of breakeven point of marigold crops for seeds in conventional and organic farming system: Forecast 2017/2018 - Rozi Liliana Berevoianu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
Marigold (Tagetes) is of importance both as a decorative plant and plant used in the cosmetic and pharmaceutical industry, with recognized medicinal properties. This paper presents a scientific approach to the methods required forthe analysis of the economic efficiency of marigold seed culture in conventional and organic farming system - forecast 2017/2018. Thus, theoretical and methodological measurement of technical - economic processes and phenomena needed for the determination of the costs of production, market price and the level of profitability per unit of product was achieved using a system of specific indicators. These indicators may be classified into specific indicators, result indicators and profitability indicators (profit, return rates, breakeven point, etc.). The results of scientific research can have positive influence over the decisions necessary for the future production cycle for cultivating marigold for seeds in conventional and organic farming system.
Keywords: O12; Q14; Q57; 330; economic efficiency; profitability threshold; marigold seed culture